The effect of palm oil trimethylolpropane ester on extreme pressure lubrication. (February 2014) - Zulkifli, NWM; Kalam, MA; Masjuki, HH; Mahmud, KAH Al; Yunus, R
This paper presents the experimental results for the extreme pressure characteristics of a palm oil-based trimethylolpropane (TMP) ester blended with paraffin oil obtained using a four-ball machine. The load and speed of the sample were set between 20–120 kg and 1770 rpm, respectively. TMP ester produced from palm oil is biodegradable and has high lubricity properties, such as a higher flash point temperature and viscosity index. It has an affinity to surface asperities, which reduces wear between sliding contacts. Based on the calculation, it was found that majority of the oils in boundary regime and mixed elastrohydrodynamic regime. For the same contact load, the film thickness with TMP100 is 70% thicker than that with paraffin oil. In addition to that, test results revealed that (1) for all the used lubrication oils, TMP ester blended with paraffin provide better surface protection compared to paraffin oil. (2) Even though, TMP100 has the highest film thickness, at low load the wear is higher. Surface morphology test was conducted using scanning electron microscope and surface roughness tester. It was found that severe corrosive wear occurred at TMP100 which is probably due to the high oxygen content compared to other lubricant.